Powers Of Nigeria's Anti-Corruption Institutions In Combating Bribery: Law And Practice - Saphy Lal Bullu (Corruptio, 2025)
This paper assesses the efficacy of Nigeria's anti-corruption institutions—the Independent Corrupt Practices and Other Related Offences Commission and the Economic and Financial Crimes Commission—in curbing bribery activities that are well-controlled at all levels. Each institution plays its major role in making sure the purposes of its establishment are well met. However, the impression of corruption persists in Nigeria, damaging the nation's reputation and fostering an image of profound moral decay. Findings show that, since 1999, successive Nigerian administrations have sought novel anti-corruption measures. The Transparency International Corruption Report ranges from 2020 to 2023; Nigeria's ranks were between 136 and 140. Such records indicate that the war against corruption is a limited in progress. The current position of Nigeria ranks 140th out of 180 countries, with a score of 26/100, demonstrating that corruption remains a significant issue despite the presence of numerous anti-corruption agencies. This article employs qualitative and quantitative methods to analyse existing data and assess the effectiveness of Nigerian institutions in combating bribery. Such methodology assists in identifying gaps in enforcement, institutional weaknesses, and the impact of political interference as key barriers to success. Recommendations include strengthening legal frameworks, enhancing transparency, and promoting public awareness to foster a culture of accountability within Nigeria.